Penegasan Peran Negara dalam Pemenuhan Hak Warga Negara Atas Air - Kasim, Helmi (Jurnal Konstitusi, 2015)
This writing analyses access to water not merely as a right but as human  rights. Since the right to water constitues human rights, then constitutionally, the state, mainly the government, is obliged to respect, fulfil and protect that right. In order that the government can perform its obligation to fulfil the right of citizens   to water, the sate should put control of water under the power of the state. Thus, there are two perspectives in fulfilling the rights of citizens to water, human rights perspective and the perspective of state control. From the perspective of human rights, the 1945 Constitution has stipulated the obligation of the state in fulfilling the human rights of citizens including the right to water as stated in Article 28I paragrahp (4). From the perspective of state control over water resources, the 1945 Constitution has also determined constitutional standard as stipulated in Article 33. This concept of state control based on Article 33 has been interpreted by the Constitutional Court in its decisions. Specifically, in the decision concerning the law on water resources, the Court returned control over water to the state. The Court  set some limitations on how to utilize water resources. Private corporations are still allowed to participate in water management with strict conditions. The enhancement of this control by the state over water is intended to guarantee the fulfilment of the right of citizens to water. As an idea, monopoly of the state over water resources might be also be considered just like monopoly of state over electricity.